BNF 71 - Alshareifi, Murtadha (London : BMA, 2016)
This biannual publication provides details on all medicines currently available on the UK market, with particular reference to their uses, contraindications, side effects, dosage and relative cost.
Keywords: Pharmaceutical; Pharmacology -- Great Britain; Pharmacopoeias -- Great Britain; Medicine -- Formulae, receipts, prescriptions